Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Efficient sludge reduction and phosphorus recovery in innovative coupled sequencing batch and worm reactor Process: Performance, mass balance and metagenomic mechanisms - Jingjing Zhang; Lipin Li; Xuanhe Yang; Siqi Chen; Zhe Li; Rui Li; Chunlei Wang; Yu Tian (Bioresource Technology, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Long-term cattle manure application rebuilds topsoil buffering capacity and mitigates fertilizer-induced acidification in Mollisols - Yafei Su; Wenbin Bao; Zhenhua Yu; Xiaojing Hu; Changkai Liu; Rui Fang; Junjie Liu; Jian Jin; Guanghua Wang; Xingyi Zhang; Yuriy Kravchenko; Xiaobing Liu; et al. (Agriculture, Ecosystems & Environment, 2026)

Pickering emulsions stabilized by rice bran protein particles-glycyrrhizic acid complexes: structural characterization, stability assessment, and curcumin delivery performance - Lang Cai; Rui Wang; Yufei Li; Shixin Song; Lei Yu (Food Chemistry, 2026)

Study on the O2 migration pathway and critical product formation mechanism in the water immersion coal oxidation - Guo-yu Shi; Xin-xiao Lu; Guan Wang; Zhao Yang; Long He; Rui-nan Zhang (Fuel, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Design of a biomimetic walking wheel inspired by reindeer hoof morphology and its snow-terrain locomotion performance - Kaixiang Chen; Rui Zhang; Mingxi Yu; Huailiang Wang; Hao Pang; Lige Wen (Cold Regions Science and Technology, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Aluminum mineral transformation drives reacidification and metal remobilization in a neutralized acidic pit lake - Junyi Gu; Lu Zhang; Ziyi Li; Rui Deng; Zijie Yu; Bo Wang; Zhengbo Yue; Jin Wang (Water Research, 2026)

Selective mobilization of particulate phosphorus via lacustrine groundwater discharge: a hidden pathway in lake nutrient budgets - Wenkai Qiu; Yao Du; Yetong Liu; Wenhui Liu; Xiaoliang Sun; Yu Yang; Chang Liu; Yiqun Gan; Rui Ma; Yanxin Wang (Water Research, 2026)

Advanced electric field technologies for postharvest preservation of fresh fruit and vegetables: Applications, mechanisms and future perspectives - Ben Yu; Dongyang Xu; Tingshi He; Jiangshan Qiao; Junhu Cheng; Xin-An Zeng; Rui Wang (Postharvest Biology and Technology, 2026)

Microbiome dysbiosis and metabolic reprogramming in kiwifruit peel during Botrytis cinerea infection - Jingsheng Chen; Rui Ma; Yu Zhao; Yuan Sui; Zhuo Chen; Xianmei Xiao; Zhenshuo Wang; Jia Liu (Postharvest Biology and Technology, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Bearing capacity envelopes of wide-shallow bucket foundations in sand under combined horizontal and moment loading - Run Liu; Rui Zhou; Xiang-chuan Meng; Yu Wang (Ocean Engineering, 2026)

Viscoelastic response of composite tensile armor layers in flexible risers under axial random loading - Rui Bao; Chen An; Ming Wang; Yu Zhang; Changyun Li (Ocean Engineering, 2026)

Catalytic ozonation with N, S co-doped sludge biochar for decontamination: Performance and mechanistic insights - Xinyi Tao; Weiwei Chen; Xuehong Fan; Rui Hu; Xuejian Wang; Shiquan Sun; Yu-Hong Cui; Zheng-Qian Liu (Journal of Environmental Chemical Engineering, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

One-step hydrophilic network for simultaneous boost in scaling prone cation removal and resistance to organic fouling of nanofiltration membranes - Rui Yu; Haonan Zhang; Yanqi Gan; Xupan Wang; Tian Wang; Jiahe Li; Mengqi Shi; Chenxi Dong; Feng Wu (Journal of Environmental Chemical Engineering, 2026)

Enhanced photothermal catalytic oxidation of cyclohexane over a S-scheme CoAl2O4/WO3-x heterojunction with LSPR effect-induced hot electrons - Kuan Wang; Kai-Xiong Dai; Yu-Rui Chao; Yue Yang; Xin-Peng Li; Zhen-Hong He; Weitao Wang; Huan Wang; Zhao-Tie Liu (Journal of Environmental Chemical Engineering, 2026)

Tuning alkyl side chains in cyclohexyl-functionalized diglycolamides for efficient strontium separation: An experimental and theoretical study - Yiting Wang; Qiao Yu; Hang Zhou; Rui Li; Qiaoyin Huang; Die Huang; Songdong Ding (Hydrometallurgy, 2026)

Effect of liquefaction solvent, catalyst sulfidation method and H2S on mild liquefaction behaviors of Jiangna coal over Fe-based catalysts - Jiaqi Yu; Yuxin Wen; Shuo Wang; Rui Zhang; He Yang; Yang Li; Xingxing Xiao; Yining Guan; Haoquan Hu; Lijun Jin (Fuel, 2026)

Climate and soil shape Daqu wheat quality and seed microbiome via rhizosphere taxa and microbial assembly - Kangjie Yu; Shuanghui Wang; Hanrui Shi; Rui Luo; Zijian Chen; Yi Xia; Qingdong Zeng; Yi Ma; Dejun Han (Food Research International, 2026)

Designing sustained-release sodium carriers: Oil-modified starch gels enhance the texture and delay sodium release in low-sodium shrimp protein gels - Menghan Wang; Yang Li; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Chemistry, 2026)

Synergistic effect of alkaline and heat treatment in inhibiting syneresis of CaSO₄-induced cold-set peanut protein isolate gel: Insights into structural modifications and gelation kinetics - Jing Chen; Rui Li; Zining Fan; Yu Wang; Yuntao Wang; Yanhong Bai (Food Chemistry, 2026)

Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Amplitude-controlled dynamic structural colors on wrinkling surfaces for facile multilevel strain-resolved optical encryption - Dengchong Feng; Shirui Wu; Yuxin Liu; Qi Guo; Rui Chen; Yu Chen; Yuzhao Yang; Haiqiang Wu; Zhiquan Zhao; Shaolin Lu; Zetong Ma; Cheng Wang; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Synergistic regulation of photosynthetic efficiency at physiological and transcriptional levels in Ottelia acuminata under single and combined nitrogen and phosphorus treatments” [Biores. Technol. 446 (2026) 134212] - Xiong-Li Zhou; Ni-Fei Dai; Si-Qi Wang; Rui-Zhang; Zhen-Yu Lyu; Erik Jeppesen; Liu Yang; Shi-Kang Shen (Bioresource Technology, 2026)

The impact for causal associations between common diseases and inflammatory bowel disease: a disease-wide bidirectional Mendelian randomization study - Yuxuan Sun; Zixin Liang; Zehua Ou; Lei Gao; Yong-Fei Wang; Jinqiu Yuan; Guangjun Yu; Rui Sun (Inflammation Research, 2026)
Objectives Observational studies on associations between various diseases and inflammatory bowel disease (IBD) are often limited by confounding and reverse causation. We aimed to assess potential causal relationships between a wide range of diseases and IBD, including Crohn’s disease (CD) and ulcerative colitis (UC). Methods We performed a comprehensive bidirectional Mendelian randomization (MR) analysis of 104 common diseases and IBD traits using the generalized summary-data-based MR (GSMR) approach. Genome-wide association study (GWAS) summary statistics for diseases were obtained from the MRC Integrative Epidemiology Unit, and IBD data from the International IBD Genetics Consortium. Summary-data-based MR (SMR) integrating GWAS and expression quantitative trait locus data was applied to identify pleiotropic genes associated with IBD. Results MR analyses identified 38, 34, and 52 exposures significantly associated with IBD, UC, and CD, respectively. Childhood- and adult-onset asthma showed distinct causal effects on UC and CD. Reverse MR indicated associations between IBD traits and 15 diseases, including multiple sclerosis. SMR identified RGS14 and CARD9 as pleiotropic genes linked to IBD, suggesting shared genetic mechanisms with asthma and multiple sclerosis. Conclusions These findings provide evidence for causal links and shared immune-related genetic mechanisms underlying IBD, highlighting potential targets for future research.

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

An injectable gradient hydrogel for spatially-ordered periodontitis treatment - Guichun Wang; Kaili Zhang; Wanting Huang; Rui Yu; Xinhai He; Yuxiao Wang; Chenjun Peng; Huanhuan Liu; Shuangying Gui (Chemical Engineering Journal, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Freeze-thaw damage evolution and crack propagation failure mechanism of red sandstone under non-uniform water distribution conditions - Li Wenbo; Sun Jielong; Chen Rui; Wang Yu; Wen Ziyi; Lou Bing (Transportation Geotechnics, 2026)

Paleoenvironmental response in the South China Sea from the Middle Miocene Climatic Optimum to Middle Miocene Climate Transition: Geochemical records from an isolated carbonate platform - Ning Guo; Wei Jiang; Tianlai Fan; Shendong Xu; Rui Wang; Jian-xin Zhao; Yue-xing Feng; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

LhCAT2-mediated crosstalk between reactive oxygen species homeostasis and anthocyanin biosynthesis enhances zinc tolerance in Liriodendron hybrid - Yongchao Ke; Yu Liu; Teja Manda; Tian Min; Rui Wang; Wenbin Su; Liming Yang (Journal of Hazardous Materials, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Characterization of GSTz2 involved in cyantraniliprole and emamectin benzoate detoxification in Drosophila suzukii - Yongqi Yan; Chongzhi Wang; Mingzhe Li; Shiwei Guo; Xuxing Li; Jingyan Yu; Xiaoqing Fang; Rui Bi (Journal of Asia-Pacific Entomology, 2026)

Machine learning-based geographical origin discrimination of Smilax china - Boyuan Xu; Haotian Zhong; Yan Wang; Rui Liu; Xiao Huang; Heming Wu; Lei Wang; Aiping Deng; Yong Xiao; Kun Yu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Fine-grained heterogeneous change detection in complex disaster response with wavelet-based spatial-frequency coupled learning - Yang Yang; Jun Pan; Qiqi Zhu; Rui Xu; Xiaoyu Yu; Junli Li; Mi Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Instability-driven flame propagation dynamics of premixed hydrogen-ammonia deflagration in a closed duct with obstacles - Rui Xie; Zhi Wang; Xianyu Yu; Liuqian Zhu; Yang Lin; Junyi Li; Bobo Shi (Fuel, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Ultrasonically treated pea starch modulates oil absorption in corn starch-based deep-fried products: Insights into gel network architecture, interfacial behavior, and molecular dynamics simulations - Menghan Wang; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

A narrow-bandgap organic photothermal material enabling efficient solar driven sustainable electricity-water cogeneration - Xiaoqing Liu; Bingpeng Guo; Rui Wei; Huijun Kong; Jiahui Yu; Baolei Wang; Weiyan Li; Jingyue Zhang; Chuanying Wang; Zhongqian Song; Changxiang Shao (Chemical Engineering Journal, 2026)

Multi-source accumulation pathways and drivers of soil organic carbon in coastal saltmarsh wetlands - Rui Zhong; Jiaming Yao; Lijie Pu; Jiayi Xie; Jiawei Tao; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Limin Yu; Gaili He; Sihua Huang (CATENA, 2026)

Decoding the survival strategy of Parachlorella sp. MP1: Genomic basis and physiological adaptations to acidity and heavy metals in acid mine drainage - Meichen Wang; Lu Zhang; Zhengbo Yue; Zijie Yu; Rui Deng; Jin Wang (Bioresource Technology, 2026)

Dynamic changes in antibiotic resistance genes during sludge composting under functional membrane coverage: Insights into key physicochemical factors and succession of host microorganisms - Rui Cai; Yunzan Wang; Wenbo Yu; Jiakuan Yang (Biomass and Bioenergy, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Application research of OBN data in fluid identification based on P-S Wave forward modeling analysis - Rui Wang; Yu-Jie Wang; Shu-Mei Yan (Applied Geophysics, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

Asymmetric atmospheric secondary circulation response to a sea surface submesoscale cold filament - Jun Yang; Ziqi Zhang; Jen-Ping Peng; Dongxiao Wang; Chunhua Qiu; Rui Shi; Mingming Shao; Shichang Zhao; Fei Yu; Yihua Luan (Science China Earth Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Effects of Alhagi sparsifolia root content and soil moisture content on soil deformation and strength under different freeze-thaw temperature conditions - Meixue Zhang; Qinglin Li; Xuanbing Luo; Wenjuan Chen; Rui Wang; Shuailong Yu; Guang Yang (Soil and Tillage Research, 2026)

Retraction notice to “Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period” [Sci. Total Environ. 906 (2024) 167622] - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Transgenic CncC overexpression confers low-level but broad-spectrum insecticide resistance in Plutella xylostella - Huichao Wang; Shiqi Chen; Rui Hu; Zhenyu Cheng; Yu Shi; Shuwen Wu; Xingliang Wang (Pesticide Biochemistry and Physiology, 2026)

Asymmetric diamide resistance conferred by ryanodine receptor G4946E/V mutations in Plutella xylostella - Xingliang Wang; Dong Jiang; Rui Hu; Shuwen Wu; Yu Shi; Yihua Yang; Yidong Wu (Pesticide Biochemistry and Physiology, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Initial exploration of the health effects on Qinghai-Tibetan Plateau yaks following short-term exposure to polystyrene microplastics: Analysis of rumen microbiota, host metabolism, antioxidant function and inflammatory responses - Penghu Zhang; Yanbing Zhu; Zhisheng Wang; Peiqiang Yu; Bai Xue; Lizhi Wang; Rui Hu; Huawei Zou; Yahui Jiang; Jianxing Xiao; Cui Tan; Fali Wu; et al. (Journal of Hazardous Materials, 2026)

Resistome risks of biological wastewater treatment communities: A global dataset of activated sludge, anaerobic digestion, and anammox - Min Xu; Shengchun Qi; Xiaofan Yu; Shiyi Han; Rui Xiao; Jianhua Guo; Changzhi Wang; Ning Zhu; Huijie Lu (Journal of Hazardous Materials, 2026)

Spatial patterns of climatic and ecological effects of photovoltaic power plants in Northwest China - Li Yu; Rui Chang; Wenjiang Huang; Biyao Zhang; Peng Lu; Yang Wang; Junqing Zheng (Journal of Environmental Management, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Micritization mechanism in penecontemporaneous carbonate rocks: coupled C − Ca cycles and constraints from diagenetic environments - Yunfeng Zhang; Menghao Zhu; Wen Yan; Haizhou Qu; Kexin Guo; Weihai Xu; Xiyang Zhang; Fei Tan; Yu Tang; Rui Wang; Guanghui Wu; Shuai Huang (Geochimica et Cosmochimica Acta, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Euglena gracilis and paramylon attenuate hyperuricemia and protect against renal injury in mice - Tao Yu; Kaikai Zhang; Rui Hang; Weiliang Wang; Jingli Xie; Wenmin Bai; Yuanguang Li; Minxi Wan (Food Bioscience, 2026)

Experimental investigation and microscopic-element modeling of shear behavior in the initial non-contact state of jointed rock - Qiaojuan Yu; Mingxiang Cao; Shigui Du; Changshuo Wang; Jibo Qin; Rui Yong (Computers and Geotechnics, 2026)

Geometry-programmed microcapsules for rice-leaf interface pinning and targeted fungicide delivery - Xiquan Ding; Lei Wang; Meng Yu; Hongwei Li; Yinmin Wang; Xinyu Guo; Yucheng Gu; Hongyan Zhang; Xuemin Wu; Rui Zhao; Yong Xu (Chemical Engineering Journal, 2026)

Mechanistic study on direct oxidation of xylose to xylonic and xylaric acids in base-free medium - Yinghao Wang; Wei Yu; Zhaozhe Li; Rui Min; Wenmao Zhang; Chunmei Li; Feng Du; Wenjuan Yan; Xin Jin; Chaohe Yang (Chemical Engineering Journal, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Calculation of hydrogeological parameters based on a high-flow long-duration water release test of multiple deep boreholes, Xiadian coalfield, North China - Fang Li; Rui Luo; Zhijia Yu; Wubin Gao; Jianggen He; Yu Ping; Shiyuan Tian; Zihan Wang; Tao Cheng; Colin G. Farquharson; Xinyi Wang (Hydrogeology Journal, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Research trends in COPD–associated invasive pulmonary aspergillosis over the past two decades: a bibliometric and topic modelling analysis - Xiaowen Wu; Rui Wang; Jing Tan; Jiaxiang Li; Zhiyue Yu; Ming Gao; Limei Geng (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Superposition Effects of Fire Exposure and Water Extinguishing on Fracturing Mechanisms and Mechanical Behavior of Granitic Building Stone - Fei Wang; Zhuang Xu; Heinz Konietzky; Liqiang Ma; Yu Pan; Qingyou Zhu; Rui Pang; Benguo He (Rock Mechanics and Rock Engineering, 2026)

Structure, assembly, and biological assessment of microbial communities based on eDNA metabarcoding in the continuous river-estuary-sea system of the Yellow River Estuary, China - Gang Xie; Xiaoxia Yu; Ning Zhang; Jie Li; Rui Wang; Yu Wang; Xinlei Li; Dan Li; Wanting Wang; Shilong Ren; Yi Zhu; Guoqiang Wang (Marine Pollution Bulletin, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

AI-driven monitoring strategy optimization for nutrient-polluted groundwater in a desert site in Northwest China - Yuting Yan; Yu Liu; Baocai Tong; Jinsheng Wang; Rui Zuo; Yuyu Wan; Yuanzheng Zhai; Xu Han (Journal of Hydrology, 2026)

Mobile phone cases as hotspots for perfluoroalkyl substances and pathogenic bacteria: An analysis based on user habits - Zhimin Xu; Zheng Lin; Runtong Huang; Rui Du; Shuai Xiao; Shunan Zhang; Heru Pramono; Yifan Wang; Renqiang Yu; Meijing Lan; Lei Wang (Journal of Hazardous Materials, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

A versatile colorimetric array sensor based on FeCu-based prussian blue analogue heterostructures for efficient discrimination of tetracycline antibiotics and rapid identification of urinary tract infection pathogens - Dan Wu; Xin-Yu Cheng; Chao-Man Wang; Ya-Nan Kong; Shu-Chang Zhao; Rui-Lin Liu (Journal of Hazardous Materials, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Endogenous nitric oxide production induced by pulsed electric field modulates postharvest quality of mango - Ben Yu; Runyu Yao; Dongyang Xu; Tingshi He; Wenhao Xiao; Wenhong Gao; Junhu Cheng; Zhong Han; Xin-An Zeng; Rui Wang (Food Research International, 2026)

Effects of Hofmeister cation series induced by different alkalizers on the production, structural and functional characteristics of low-sodium soy protein fractions - Yu Peng; Rui Wang; Mo Li; Xin Wen; Yuanying Ni; Sirinan Lasrichan (Food Hydrocolloids, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Less is more: Retaining uncyclized o-quinone group in quinone/pyrazine hybrid molecules for high-energy zinc–organic batteries - Han Yan; Rui Wang; Jinyin Yu; Xiaotang Gan; Housheng Gong; Qian Wang; Zewen Zhu; Xiang Tang; Zhiping Song (Chemical Engineering Journal, 2026)

Ah-level small-molecule proton batteries enabled by a cost-effective gradient-porous composite separator - Yu Li; Rui Li; Xinyu Wang; Mengxiao Li; Junjie Wang; Huige Ma; Mengjing Wu; Haiping Yu; Bei Wang; Huijie Wang; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

A multi-strategy integrated heuristic algorithm for the container relocation problem in automated container terminal yards - Yipeng Jiang; Yong Zhang; Lei Zhang; Zhen Li; Chengji Liang; Rui Zhao; Yu Wang; Panlong Wang (Frontiers in Marine Science, 2026)
As the operational scale of automated container terminals continues to expand, the impact of the container relocation problem on operational efficiency and cost has be-come increasingly significant. To address the issues of excessive relocations and low operational efficiency during container retrieval within a bay, a container relocation optimization model for the yard is developed. On this basis, a bay-oriented heuristic algorithm is proposed by incorporating practical operational rules and operational experience. The algorithm prioritizes empty stacks, non-blocking stacks, and stacks with the minimum number of blocking containers. It further integrates the nearest-placement rule and safety height constraints to achieve efficient and rational relocation decisions for blocking containers. Numerical experiments with different problem scales are conducted to validate the effectiveness of the proposed method. The results show that, in small-scale instances, the proposed algorithm effectively reduces the number of relocations. In large-scale instances, its advantage becomes more pronounced as the problem size increases. Compared with the traditional nearest-placement rule, the proposed algorithm consistently achieves superior performance across different scales: the number of relocations is reduced by up to 15, the relocation rate decreases by an average of 56%, and the operational cost is reduced by approximately 35.85% on average.

ERK1/2 activation in anti-inflammatory effects and underlying signaling mechanisms - Kaiwen Tao; Lin Xu; Chao Cheng; Fukang Yuan; Yicheng Yu; Lidan Zhang; Runmin Li; Rui Xia; Haibei Dong; Xingqi Wang (Inflammation Research, 2026)

Heterogeneity of REE distribution revealed by rare-earth phosphate minerals in Chang’e-6 lunar soil - Zhenhao Hu; Rui Li; Jingwen Liu; Yang Li; Tao Chen; Qinglong Yu; Xi Wang; Baochen Yang; Jingyan Xu; Xiongyao Li; Jianzhong Liu; Ziyuan Ouyang (Acta Geochimica, 2026)

An Attention-Enhanced Temporal Convolutional Network for Surrounding Rock Deformation Prediction in Mountain Tunnels - Rui Su; Yitao Yang; Guowen Xu; Ziqian Yang; Jie Yu; Ruohui Wang; Dong Zhou; Zhuolin Wu (Rock Mechanics and Rock Engineering, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Long working hours increase the risk of insufficient dietary diversity: Findings among online ride-hailing drivers - Binshuo Hu; Cheng Chang; Xin Song; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Hong Yu; Li Guan; Dongsheng Niu; Jue Li; Rui Guan; Tenglong Yan (Appetite, 2026)

Geochemical signatures of REE + Y during dolomitization of aragonitic corals: Insights from high-temperature experimental simulations - Songye Wu; Rui Wang; Chuntong Liu; Hui Hua; Xingchi Li; Qiushuang Qin; Kefu Yu (Sedimentary Geology, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Lignin-based sunscreen materials: A review of mechanisms of action, precision modification strategies, multifunctional application advances, challenges and prospects - Yuan Chen; Zibo Yu; Rui Tang; Jiayi Sun; Xigao Jian; Jinyan Wang; Xiaozhou Zhang; Xing Wang; Jingyu Xu (Journal of Environmental Chemical Engineering, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Trends and coupling coordination of agricultural carbon effects and food security in the Yellow River Basin, China - Jiuran Nie; Lei Yu; Bingyao Zhang; Yu Li; Mo Li; Rui Jing; Liuyue He; Jun Wang; Yanlai Zhou (Journal of Cleaner Production, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Centennial evolution and driving mechanisms of the Baiyangdian Wetland: A multi-source data reconstruction and interpretable machine learning approach - Haoyang Wang; Chunyi Li; Yangying Zhan; Meng Li; Yu Ning; Junxuan Li; Rui Meng (Journal of Cleaner Production, 2026)

Accelerated peroxymonosulfate activation via internal electron migration within Co3O4/Bi2Fe4O9 for efficient phenol degradation - Bo Liu; Hangyu Shi; Yawei Wang; Rui Liu; Shuangshuang Zuo; Qianqian Nie; Lei Yang; Hesheng Yu (Journal of Environmental Sciences, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

A detoxifying multi-strain probiotic formula attenuates toxicity induced by heavy metals and phthalates - Rui Xiao; Yaqi Yu; Deshan Ning; Zehua Chen; Chuguang Ning; Leilei Yu; Shumao Cui; Jianxin Zhao; Gang Wang; Yong Zhou; Xing Jin (Food Research International, 2026)

Systemic crosstalk between liver and brain is associated with microplastic-induced neurobehavioral toxicity in zebrafish - Zhimin Xu; Zheng Lin; Yifan Wang; Lei Wang; Runtong Huang; Rui Du; Xinya Kang; Xueqing Chen; Shaohua She; Zhihao Xu; Shuai Xiao; Renqiang Yu (Environmental Pollution, 2026)

Improved mitigation of reverse osmosis membrane biofouling via synergistic UV light-emitting diodes and chlorine disinfection - Yu-jia Gao; Rui-ning Wang; Shi-tong Yu; Ke-fan Cao; Xu-Cheng Cai; Yu Hong; Yun Wang; Wei E. Huang; Nozomu Ikuno; Nakata Koji; Hong-ying Hu; Yin-hu Wu (Desalination, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Anti-adhesion nanofiltration membranes via a fluorine-rich microenvironment for broad-Spectrum micropollutant removal - Yanqi Gan; Rui Yu; Xupan Wang; Tian Wang; Jiahe Li; Feng Wu; Mengqi Shi (Chemical Engineering Journal, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Performance analysis and experimental study of flexible opening-closing single garlic seed metering device based on DEM-MBD coupling - Zhengzhong Li; Hua Zhou; Yinping Zhang; Fangyuan Lu; Xian Wang; Jiaye Li; Yanjun Li; Yangting Hu; Rui Yu (Computers and Electronics in Agriculture, 2026)

Model scale approach to assess the seakeeping performance of a foil-assisted unmanned catamaran - Bing Zheng; Qiaowen Yu; Shigang Wang; Weimin Chen; Zhiyuan Geng; Rui Deng (Ocean Engineering, 2026)

Drought-induced disaster Chains: A global perspective of propagation probabilities and mitigation priorities - Huicong Jia; Fang Chen; Rui Li; Yu Chen; Lei Wang (Journal of Cleaner Production, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Mechanism and geological significance of methane adsorption and desorption in deep dry and wet high-rank coal under supercritical conditions - Jie Huang; Shuangbiao Han; Yu Qiao; Yongping Wan; Zhenchuan Wang; Hongtao Gao; Liang Qiao; Yurun Rui (Fuel, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

U-shaped multi-scale feature fusion network for three-dimensional geological modelling and uncertainty assessment - Yu Zhang; Rui Wang; Jian Chu; Mingchun Guo (Engineering Geology, 2026)

Mechanical-thermal -electrical-magnetic integration in aramid composites via binary inorganic synergy - Junchao Ren; Chenglei Huang; Rui Tan; Jianlong Chen; Mengde Huang; Shijing Song; Chengyu Yu; Hanwu Lei; Lu Wang; Bin Li; Qingfa Zhang (Chemical Engineering Journal, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Engineering Escherichia coli cell Factories for continuous 5′-cytidine monophosphate production via biofilm-anchored dual-enzyme cascade catalysis - Wenjun Sun; Shiya Zhu; Qiwei Dong; Shuyan Tang; Qingguo Liu; Yu Sha; Tianpeng Chen; Rui Wang; Yong Chen; Hanjie Ying (Bioresource Technology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

BTEXS metabolites and lung dysfunction in petrochemical workers: Dose-response relationships and the mediation of oxidative stress - Dongsheng Wang; Rui Ma; Minghui Xiao; Zhaorui Zhang; Han Yang; Yanrong Lv; Shaorui Yu; Xiumei Xing; Shanfeng Dang; Qifei Deng; Xiaoyu Mao; Qiansheng Hu; et al. (Atmospheric Pollution Research, 2026)

Deletion of the SHORT Syndrome Gene Prkce Results in Brain Atrophy and Cognitive and Motor Behavior Deficits in Mice - Yu-Long Bao; Wei-Peng Duan; Yan Yang; Zhijie Lin; Ying Shen; Rui Zheng; Xin-Tai Wang (Neuroscience Bulletin, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

Responses of Phaeodactylum tricornutum to short-chain chlorinated paraffins: growth inhibition, photosynthetic damage and oxidative stress - Rui Shi; Wei Chen; Yujun Hu; Bingjian Chen; Xiaoxiao Yu; Hui Huang; Dan Wang; Shunxin Hu (Frontiers in Marine Science, 2026)
Introduction Short-chain chlorinated paraffins (SCCPs) have garnered increased attention due to higher persistence, bioaccumulation, long-distance transportation potential, and heightened toxicity to aquatic species and mammals. Methods This paper evaluated the toxic effects of SCCPs on P. tricornutum during a 96-hour acute exposure experiment, focusing on growth inhibition, photosynthetic parameters, and oxidative stress responses. Results Results showed that at the environmental concentration (0.001 mg/L), SCCPs exerted no significant effects on the growth and photosynthesis of P. tricornutum . However, higher concentrations (2, 4, and 8 mg/L) exposure resulted in a pronounced, dose-dependent growth inhibition, with inhibition rates reaching 37.43%, 53.25%, and 54.47% (p < 0.05), respectively. SCCPs stress disrupted the photosynthetic system, leading to reduction in the contents of chlorophyll a, chlorophyll c and carotenoids. Key photosynthetic pigments were depleted, and Photosystem II (PSII) efficiency (Fv/Fm, Y(II), rETRmax) was markedly suppressed. Furthermore, SCCPs exposure induced oxidative damage, as evidenced by elevated reactive oxygen species (ROS) and malondialdehyde (MDA) levels. Mitochondrial damage led to insufficient energy supply, resulting in decreased antioxidant enzyme activity. Discussion Collectively, these findings establish that high concentrations of SCCPs inhibit algal growth and photosynthesis through a dual mechanism involving direct photosynthetic disruption and the induction of oxidative damage.

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Dynamic analysis for monopile offshore wind turbine under combined wind-wave-seismic loading: Effects of clay cyclic degradation and shakedown - Kehao Chen; Rui Pang; Cun Hu; Long Yu; Tianju Wang; Yang Zhou; Bin Xu (Ocean Engineering, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Renal macrostructural and hilar Doppler hemodynamic stability during a 7-day head-down tilt bed rest: an exploratory ultrasound-based study in humans under simulated microgravity - Fengxia Yu; Xia Ma; Yawen Liu; Rui Wang; Yiwen Wang; Peng-Gang Qiao; Wei Zheng; Xiangdong Hu; Linxue Qian; Pengling Ren; Zhenchang Wang (Life Sciences in Space Research, 2026)

Ecosystem vertical structural complexity and soil nutrition synergistically enhance extreme drought resistance via water use efficiency in the Yangtze River Basin - Yue Cao; Xinyi Hao; Fei Yu; Rui Wang; Huiwen Li (Journal of Environmental Management, 2026)

Lanthanide doping induces surface lattice oxygen activation in CoMn2O4 hollow cubes to enhance NOx reduction - Yu Zhang; Ying Wang; Rui Wang; Ling Zhao (Journal of Environmental Chemical Engineering, 2026)

Hidden acidification beneath soil-covered mine waste dumps: links to oxygen-limited sulfur oxidation - Ziyi Li; Zhengbo Yue; Junyi Gu; Shu Wang; Lu Zhang; Zijie Yu; Rui Deng; Jin Wang (Journal of Environmental Management, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Surface aging of Ti-based MXene attenuates mitochondrial toxicity via suppressed cellular uptake and reactivity - Rui Zhang; Xiaodi Li; Yujiao Liu; Xuan Mao; Yongyi Wei; Yu Wang; Xiaofei Zhou; Jianbo Jia (Environmental Pollution, 2026)

Variance reduction function modeling for a potential circular slip surface in spatially variable slopes - Lihang Hu; Rui Zhang; Gang Wang; Yang Li; Zhi Li; Faxin Li; Junyan Yu; Kiyonobu Kasama (Engineering Geology, 2026)

Full-active Self-assembling nanoPROTACs for betulinic acid-amplified Protein Degradation and Enhanced Rheumatoid Arthritis Therapy - Xingpai Cai; Yonggang Zhao; Weijie Zhang; Yu Cao; Penghui Zhang; Rui Wang; Ningli Zhang; Weijun Huang; Nannan Lu; Jinming Zhang; Zhenbao Li (Chemical Engineering Journal, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Synergistic regulation of photosynthetic efficiency at physiological and transcriptional levels in Ottelia acuminata under single and combined nitrogen and phosphorus treatments - Xiong-Li Zhou; Ni-Fei Dai; Si-Qi Wang; Rui-Zhang; Zhen-Yu Lyu; Erik Jeppesen; Liu Yang; Shi-Kang Shen (Bioresource Technology, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Technological evolution and industrial scaling of Spirulina in China: a four-decade review - Kexin Xu; Ronglian Xing; Kang Wang; Song Qin; Zhili Yu; Hongxia Zhang; Rui Li; Zhen Yu; Lihong Chen (Journal of Applied Phycology, 2026)

Establishment and application of multiple cross displacement amplification coupled with lateral flow biosensor (MCDA-LFB) for visual and rapid detection of Candida glabrata - Yan Yuan; Yuhong Zhou; Yanfeng Zhou; Rui Ye; Jingrun Lu; Yizhe Wang; Fang Wei; Fukuan He; Honglan Yu; Yu Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Long-term reclamation enhances soil organic carbon accumulation via mitigating salinity and alkalinity in coastal saline soils - Wei Zhu; Shiguo Gu; Xin Zhang; Xuan Yu; Shuanghuang Yu; Xiangping Wang; Rui Jiang; Xiangtian Meng; Rongjiang Yao (Agriculture, Ecosystems & Environment, 2026)

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Promoting Aquatic Animal Health and Water Quality: A Systematic Review on Probiotics, Prebiotics and Synbiotics in Aquaculture - Yaxin Wen; Miao Wang; Haoran Wang; Shilin Liu; Ronglian Xing; Hongxia Zhang; Lihong Chen; Rui Li; Zhen Yu (Fishes, 2026)
Background: Aquaculture, a vital component of global food security, faces sustainability challenges due to intensive farming practices, including water pollution, disease outbreaks, and antibiotic overuse. Probiotics, prebiotics, and synbiotics have emerged as eco-friendly alternatives to antibiotics. However, research results remain heterogeneous across aquatic species and intervention strategies. Methods: Following PRISMA 2020, we searched two databases (up to January 2026) for in vivo trials. Two reviewers screened and extracted data, and 177 eligible studies were ultimately included, covering single-/multi-strain probiotics (SSP/MSP), live/inactivated microbial preparations, and diverse synbiotic formulations. Results: Among 177 studies, Bacillus spp. were the most widely reported and effective probiotic strains. MSP and synbiotics exhibited superior efficacy in boosting aquatic animal growth performance and disease resistance over SSP in 68% of the included trials. Probiotics act through the competitive exclusion of pathogens, immune modulation, and enhanced digestive enzyme activity; prebiotics selectively stimulate beneficial gut microbiota, improving nutrient absorption and immune function through metabolites such as short-chain fatty acids; synbiotics combine the advantages of both, exerting synergistic effects. Furthermore, as water additives or fermented feed ingredients, probiotics reduce nitrogenous waste and organic pollutants, contributing to bioremediation. Conclusions: All three additives are effective. Standardized application protocols and long-term trials are needed for sustainable aquaculture. This review provides a unified evidence-based foundation for the rational use of these additives in aquaculture.

Ferrate-assisted nonthermal plasma for efficient PFOA degradation in landfill leachate: Mitigating bulk organic interference and enhancing application potential - Changtao Chen; Zhuofan Yu; Rui Zhang; Xuetong Yang; Qintong Wang; Yuxian Ji; Xiaoyu Cheng; Jun Li; Anton Nikiforov; Stijn W.H. Van Hulle; Bo Lai (Water Research, 2026)

Nutrient regimes shaping the diatom-dinoflagellate interdecadal succession in coastal temperate waters of China - Kan Chen; Keqiang Li; Guangshen Tan; Peiyi Gao; Guangmin Zhen; Rui Yang; Kunlong Yu; Xiansheng Zhang; Xiaoru Cui; Dongliang Lu; Shanqiao Chen; Eric P. Achterberg; et al. (Water Research, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Faecalibacterium prausnitzii derived postbiotic attenuates PEDV-induced mitochondrial apoptosis through blocking viral entry - Lingcong Deng; Rui Luo; Shihan Yang; Letian Li; Nan Li; Yu Dong; Jiayi Hao; Ju Li; Anqi Deng; Xueyan Ai; Maopeng Wang; Chang Li (Veterinary Microbiology, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Global retrieval of harmonized microwave land surface emissivity leveraging multi-sensor measurements from GMI, AMSR2 and MWRIs - Jiheng Hu; Rui Li; Peng Zhang; Yu Wang; Shengli Wu; Husi Letu; Fuzhong Weng (Remote Sensing of Environment, 2026)

Mechanistic insights into low-temperature NH3-SCR over Mn-based Zr-pillared montmorillonite (Mn/Zr-PILM): Synergistic catalysis revealed by experiments and DFT - Ziwen Zheng; Huaqing Xie; Zhenyu Yu; Bin Xiao; Qingbo Yu; Kun Wang; Jiabo Zhao; Haijian Xu; Rui Guo (Process Safety and Environmental Protection, 2026)

An Integrative morphology–hormone–transcriptome analysis of uniconazole induced internode shortening in Paeonia lactiflora - Le Chen; Zhijun Dong; Rui Zhao; Yanfang Ma; Liyuan Chen; Yuxuan Wang; Jaime A. Teixeira da Silva; Xiaonan Yu (Plant Science, 2026)

Integrated metabolomics and transcriptomics analyses reveal the molecular mechanism of anthocyanin accumulation in veins and leaves of Broussonetia papyrifera under cold stress - Xiangxue Yu; Rui Ni; Dingguo Zhang; Bo Chen; Qian Li; Ziyu Yang; Chenjing Li; Fuyuan Liu; Yongtao Xia; Guoqing Hou; Guoping Wang; Pengzhi Mao; et al. (Plant Science, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Dynamic hydrogen-bond-driven thorium ion traps in sodium alginate/tannic acid beads - Dingyang Chen; Chaofan Wang; Yu Yu; Zixu Ren; Rui Zhao (Journal of Hazardous Materials, 2026)

A new method for planning long-distance trails using wilderness quality mapping and trajectory data: A case study of the Taihang Mountain National Forest Trail in China - Yunmiao Chen; Yue Cao; Zhangqian Ye; Tao Liu; Pei Wang; Yunshuang Feng; Lingyun Liao; Mingyang Lv; Zhicong Zhao; Alan E. Watson; Steve Carver; Changjia Li; et al. (Journal of Environmental Management, 2026)

Drivers of CO2 and CH4 fluxes from shallow lakes and prediction based on climate factors under global warming - Zhentao Wu; Hui Liu; Fan Yang; Rui Ran; Huimin Yu; Haonan Xu; Danyun Chen; Geng Wang; Xiaobing Pang (Journal of Environmental Sciences, 2026)

Precambrian crustal evolution of the southern margin of the North China Craton: Evidence from the Paleo–Mesoproterozoic sedimentary rock - Shuo Wang; De-Bin Yang; Xiang-Yu Yan; Ke Wu; Jian-Ning Liu; Rui-Qing Xue (Journal of Asian Earth Sciences, 2026)

Dual-Regulated Ru by alloying and Metal-Substrate interaction for Energy-Efficient hydrazine Oxidation-Paired hydrogen production - Qijing Zhang; Hongxia Yu; Siyi Wang; Haibo Li; Suyuan Zeng; Rui Li; Qingxia Yao; Qi Zhang; Ruru Chen; Lijian Meng; Konggang Qu (Fuel, 2026)

Post-thinning recovery time and litter quality co-regulate litter decomposition in mixed oak-pine forests - Shuiqiang Yu; Shizhou Ju; Rui Tan; Xiangfu Wang; Zi’ao Liang; Yu Li; Yuanhui Li; Weifeng Wang (Forest Ecology and Management, 2026)

Pulsed electric field facilitated fibrillation of soy protein isolate: preparation, characterization, and functional properties - Dong-Yang Xu; Ben Yu; Wen-Hao Xiao; Zhong Han; Rui Wang; Xin-An Zeng (Food Hydrocolloids, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Corrigendum to ‘Association of residential green space, blue space, and natural environment with osteoarthritis risk: The role of air pollution and phenotypic age acceleration’ [Environ. Res. volume 292 (2025) / 123632] - Jilong Bai; Panting Wei; Yao Zhang; Liying Wang; Rui Ren; Wenxu Wang; Difei Wang; Wan Yu (Environmental Research, 2026)

Association of residential green space, blue space, and natural environment with osteoarthritis risk: The role of air pollution and phenotypic age acceleration - Jilong Bai; Panting Wei; Yao Zhang; Liying Wang; Rui Ren; Wenxu Wang; Difei Wang; Wan Yu (Environmental Research, 2026)

pH-responsive dual MOF-on-MOF core-shell nanocarrier enables an innovative “pesticide–fertilizer integration” strategy for advanced plant disease management - Yingjian Ma; Pengkun Yan; Xiangdong Li; Meng Yu; Shouhe Pan; Yinmin Wang; Rui Zhao; Xinyu Guo; Yucheng Gu; Yong Xu; Xuemin Wu (Chemical Engineering Journal, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

Correction to: Genetic Mapping of the Wheat Dimeric α-Amylase Inhibitor Multi-Gene Family Using Allele-Specific Primers Based on Intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Glaucine suppresses IL-16/CD4 to alleviate neuropathic pain via spinal p56lck-NMDA receptor signaling - Xue Li; Rui Wang; Xiaonan Ma; Jin Yang; Shen Zhang; Zimeng Zhang; Han Jiang; Jihua Liu; Boyang Yu; Wenling Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

The microbial mechanism of the impact of grazing degradation on the soil multifunctionality of the hummock wetland on the riverscape - Xiaoai Cao; Huamin Liu; Rui Zhang; Yunhao Wen; Shan Jiang; Zhichao Xu; Lu Wen; Yi Zhuo; Dongwei Liu; Ke Yu; Lixin Wang (Applied Soil Ecology, 2026)

Comprehensive observations of carbonyls in the Northern slope of the Tianshan Mountains: Characteristics, reactivity and sources - Kexin Wang; Minghao Dong; Hanran Liu; Xin Zhang; Yunfeng Li; Yafei Wang; Rui Gao; Jingjing Zhang; Yurong Li; Yu Chen; Zhaojiang Li (Air Quality, Atmosphere & Health, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

SEAF-Net: A Sustainable and Lightweight Attention-Enhanced Detection Network for Underwater Fish Species Recognition - Yu-Shan Han; Sheng-Lun Zhao; Chu Chen; Kangning Cui; Pingfan Hu; Rui-Feng Wang (Journal of Marine Science and Engineering, 2026)
This study presents SEAF-Net, a lightweight and efficient detection network designed for low-contrast and highly dynamic underwater environments. Built upon YOLOv11n, SEAF-Net introduces three complementary structural enhancements: (1) Omni-Dimensional Dynamic Convolution (ODConv) to improve adaptive modeling of multi-scale and directional texture variations; (2) SimA-SPPF, which embeds the SimAM attention mechanism into the SPPF module to enable neuron-level saliency reweighting and effective suppression of complex background interference; and (3) GhostC3k2 to reduce redundant computation while preserving sufficient representational capacity. Evaluated on a standardized 13-class underwater fish dataset under a unified training and evaluation protocol, SEAF-Net achieves 6.1 GFLOPs, 92.683% Precision, 88.459% Recall, 93.333% mAP50, 73.445% mAP, and a 90.522% F1-score. Compared with the YOLOv11n baseline, SEAF-Net improves F1-score and Recall by 0.510% and 0.575%, respectively, while reducing computational cost by approximately 6%, demonstrating a favorable accuracy–efficiency trade-off under lightweight constraints. Ablation results further confirm that SimA-SPPF plays a dominant role in background suppression, ODConv consistently enhances deformation and directional texture modeling, and GhostC3k2 effectively controls computational overhead without degrading detection accuracy. To assess deployment feasibility, additional test set evaluations were conducted under deployment-oriented conditions using resource-limited hardware, yielding an F1-score of 88.54%. This result confirms that the proposed model maintains stable detection performance and robustness beyond training and validation stages. Overall, SEAF-Net provides an effective balance of accuracy, efficiency, and robustness, offering practical support for low-carbon, scalable, and sustainable intelligent aquaculture monitoring and underwater ecological assessment in real-world environments.

Noise Characteristics and Shallow Subsurface Structure Detection in Coastal Zones: A Case Study from Dong’ao Island, Zhuhai - Siqing Liu; Sixu Han; Yongzhi Liang; Shuji Yang; Yi Chai; Tongying Hu; Ruifeng Wu; Yu Li; Qingxian Zhao; Zengjia Li; Wei Zhang; Xianqing Wang; et al. (Journal of Marine Science and Engineering, 2026)
Shallow subsurface structure detection in coastal zones serves as a critical foundation for resource development and engineering construction. However, conventional geophysical methods exhibit significant limitations in land–sea transition zones, where pronounced “boundary effects” create substantial “exploration gaps” due to difficulties in merging terrestrial and marine datasets. To achieve truly seamless subsurface imaging across the coastal boundary, this study develops and implements an integrated cross-boundary survey approach utilizing nodal seismometers and seismic ambient noise. At Dong’ao Island, Zhuhai, we deployed a comprehensive seismic profile spanning hillside, sandbeach, and seafloor environments to evaluate the method’s applicability in complex coastal settings systematically. Results demonstrate substantially stronger ambient noise energy in submarine environments compared to terrestrial settings. All stations recorded abundant and stable high-frequency (>1 Hz) noise signals, which are adequate for shallow subsurface imaging. Rayleigh wave dispersion curves extracted via the advanced Frequency-Bessel transform method enabled inversion of a continuous 2D shear-wave velocity profile along the survey line. Bedrock interface depths determined using the Horizontal-to-Vertical Spectral Ratio (HVSR) method showed remarkable consistency with the bedrock morphology revealed by the shear-wave velocity structure, validating the reliability of our approach in coastal environments. This research successfully demonstrates the feasibility of seismic ambient noise imaging as a bridging technique for land–sea exploration, providing an efficient, environmentally friendly, and continuous technical solution to overcome coastal zone exploration challenges.

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

YOLOv11-SDiseasedFishNet:Recognition of body surface symptoms of diseased fish based on automatic combination augmentation and multi-scale feature fusion - Zijian Wu; Jian Li; Rui Shi; Hongjing Dai; Zhibo Cui; Yue Wang; Hong Yu (Aquaculture, 2026)

Removal characteristics and functional bacterial community analysis of novel two-stage integrated biological reactor and two-stage anoxic–oxic systems feeding with livestock farming wastewater - Zhenxing Zhong; Wenzhe Liu; Yanxu Zhu; Jingjing Liu; Chunjie Zhang; Rui Wang; Nanshan Yang; Xuejun Long; Peng Yu; Feixiang Zan; Xiejuan Lu; Xiaohui Wu; et al. (Journal of Water Process Engineering, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Iron: A double-edged sword of female reproductive health - Rui Mao; Dan Yin; Wenbo Lv; Die Wang; Ying Ouyang; Cuilan Zhou; Jun Liu; Suyun Li; Yunhua Zhu; Ping Yu; Hongqing Liao; Cuiying Peng (Journal of Trace Elements in Medicine and Biology, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

Biodegradable microplastics induce more soil nitrous oxide emission than conventional in semi-arid Loess Plateau - Xiaogang Li; Rui Wang; Xinran Zhang; Shengli Guo; Lei Yu; Xiaotang Ju (Journal of Hazardous Materials, 2026)

Multichannel charge separation induced by multiple internal electric fields in ReS2/CoSx/CdS hollow nanostructures for efficient photocatalysis - Qi-Rui Zhang; Yu-Long Wang; Zhi-Hao Deng; You-Long Chen; Si-Jing Ding; Liang Ma (Journal of Environmental Chemical Engineering, 2026)

Preparation of high-performance reverse osmosis membrane by “bridging” polyethylene glycol with tannic acid - Tian Wang; Rui Yu; Yanqi Gan; Zihang Zhao; Mengqi Shi; Xinxia Tian (Journal of Environmental Chemical Engineering, 2026)

Metagenomic insights into rhizosphere microbiome dynamics of Oenanthe javanica in ecological floating beds under different hydrodynamic regimes - Xuming Xu; Jiawei Wang; Chunfang Deng; Xiao Yu; Rui Nie; Siya Wang; Wei Huang (Journal of Contaminant Hydrology, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Miocene carbonate crash in the eastern Pacific: A catalyst for early rare earth element enrichment - Yayue Tang; Dengfeng Li; Fei Huang; Rui Wang; Jiewei Hu; Jinzhou Peng; Yu Fu; Xiaoming Sun (Global and Planetary Change, 2026)

Investigation of water and oxygen influence on the coal thermal decomposition entire process kinetic mechanism and gas product source tracing - Xin-xiao Lu; Guo-yu Shi; Rui-nan Zhang; Shuo Wang; Long He; Guan Wang (Fuel, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Sustainable production of Microalgae-Derived turbostratic graphene via flash Joule heating - Fuyuan Wang; Rui Huang; Yujie Yu; Shaojunyan Tan; Ruijie Yuan; Jianyong Yin; Shijie Zhang (Bioresource Technology, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Brominated organic compounds in leachate across China: Occurrence and molecular variations - Jing Zheng; Ji-Tao Lv; Yue Sun; Qing-Yu Liu; Qiu-Rui Zhang; Zi-Meng Wang; Xiao-Song He (Water Research, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Spatiotemporal characteristics of RPL24 expression in the yak oviduct and its regulatory mechanism on epithelial cell proliferation via DDX3X/DDX5 - Yanhu Wang; Yangyang Pan; Rui Ma; Yuejiao Liao; Kangle Xian; Yan Cui; Sijiu Yu (Theriogenology, 2026)

Gyrotropic magnetic effect in black phosphorus irradiated with bicircular light - Fangyang Zhan; Xin Jin; Da-Shuai Ma; Jing Fan; Peng Yu; Dong-Hui Xu; Rui Wang (Science Bulletin, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Microalgae-bacteria interactions in acidic mining pit lakes: Community assembly and environmental drivers - Meichen Wang; Jin Wang; Xin Pan; Zijie Yu; Ziyi Li; Rui Deng; Zhengbo Yue (Process Safety and Environmental Protection, 2026)

Molecular mechanism of Glutathione S-Transferase involved in resistance to multiple fungicide in Lasiodiplodia theobromae - Rui He; Jinlin Liu; Shanying Zhang; Meng Wang; Yu Zhang; Xiaoyu Liang; Ye Yang (Pesticide Biochemistry and Physiology, 2026)

Spider nest-retreat origin, diversification, and architectural plasticity link to historical and current temperature fluctuations - Rui Zhong; Jian Chang; Yunhe Wang; Haixin Zhang; Yu Peng; Ingi Agnarsson; Jie Liu (Molecular Phylogenetics and Evolution, 2026)

Mechanisms of AMF-mediated correlation between nutrient uptake and soil micropatterns in sugar beet plants under rotational and continuous cropping soil environments - Rui Chen; Yonglong Liu; Xinyi Zhang; Gui Geng; Lihua Yu; Yao Xu; Jiahui Liu; Yuguang Wang (Journal of Cleaner Production, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Molecular characterization, transcriptional profiling, and immune functional analysis of CD94 from Nile tilapia (Oreochromis niloticus) - Yijian Huang; Guoling Luo; Dandan Wu; Zhongxin Hu; Jia Cai; Bei Wang; Yishan Lu; Zhiwen Wang; Rui Song; Jichang Jian; Yu Huang (Fish & Shellfish Immunology, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Injectable glucose-responsive hydrogels with hemorrhage control and microenvironmental regulation for diabetic wound repair - Zhengyuan Liu; Zhongyang Liu; Yi Yu; Xuechen Zhang; Fangyuan Yu; Rui Song; Xing Wang (Carbohydrate Polymers, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Arbuscular mycorrhizal fungi inoculation enhances 15N uptake by rice via modifying rhizosphere and hyphosphere soil bacterial and fungal community and soil enzyme activity - Pei Chen; Yu Cheng; Rui Chen; Ning Wang; Jianguang Yu; Lihong Xue; Linzhang Yang (Plant and Soil, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)